(untitled) (Jurnal Mekanikal, 2018)
The paper describes the design and development ofa dedicated multifunction gripper for use in a robotic assembly system. It is based on the current automated assembly system operating in an actual manufacturing environment involving the assembly of parts to be incorporated in automated teller machines (ATM). The gripper that is fixed to the wrist of the robot arm is used to handle a set offerrous shafts and rubber rolls to be assembled via suitable assembly mechanisms. A comprehensive description of the gripper design process is given from the conceptual stage to the realization of the prototype including testing and evaluation.